Analyzing Free Economic Zones in Uzbekistan for Sustainable Growth - Ahn, Young-Jin; Juraev, Zuhriddin; Gu, Ji-Yeong (Faculty of Geography, Universitas Gadjah Mada, 2024)
This study examines the economic geography of Uzbekistan's free economic zones, focusing on their current significance and future prospects. It examines the historical and theoretical foundations of these zones, focusing on their role in shaping and organizing them. The study looks at the status of the free economic zones and examines their contribution to key economic indicators such as gross domestic production, trade, labor and tourism. In addition, the study uncovers the challenges faced by the free economic zones and provides targeted recommendations to effectively address these issues. The findings not only contribute to the existing economic geography literature, but also serve as a valuable resource for policy makers, researchers and stakeholders interested in promoting economic growth and regional development through free economic zones. This study provides a comprehensive analysis and a theoretical basis for understanding free economic zones in Uzbekistan and offers a broader perspective for improving their performance and potential to ultimately promote sustainable economic development in the country and beyond.